2006
DOI: 10.1002/cpp.463
|View full text |Cite
|
Sign up to set email alerts
|

Social anxiety in anorexia and bulimia nervosa: the mediating role of shame

Abstract: Objective: The close relationship between social anxiety and eating disorders has attracted considerable scholarly attention in recent years. Shame has been identified as the key emotional symptom in the link between social anxiety and social phobia. While shame is commonly recognized as a meaningful construct for understanding eating disorders, empirical research into this issue has been lacking. Thus, the objective of this study was to determine the strength of influence shame and social anxiety have in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 37 publications
2
74
0
5
Order By: Relevance
“…Jadi, selain menunjukkan hubungan antara rasa malu dan gangguan makan pada umumnya, penelitian ini juga menyoroti fokus rasa malu yang penting bagi wanita dengan gangguan makan (perilaku makan). Sejak saat itu, berdasarkan hasil review yang dilakukan oleh Goss dan Allan (2009) terdapat beberapa hasil penelitian yang terus menemukan bahwa terdapat hubungan positif antara malu (secara umum) dan patologi makan (Gee & Troop, 2003;Grabhorn, Stenner, Stangier, & Kaulfhold, 2006;Masheb, Grilo & Brondolo, 1999;Murray, Waller & Legg, 2000;Sanftner, Barlow, Marschall, & Tangney, 1995;Swan & Andrews, 2003;Troop, Allan, Serpell, & Treasure, 2008).…”
Section: ; Bulimia Nervosa (Bn); Binge Eating Disorder (Bed); Dan Eatunclassified
“…Jadi, selain menunjukkan hubungan antara rasa malu dan gangguan makan pada umumnya, penelitian ini juga menyoroti fokus rasa malu yang penting bagi wanita dengan gangguan makan (perilaku makan). Sejak saat itu, berdasarkan hasil review yang dilakukan oleh Goss dan Allan (2009) terdapat beberapa hasil penelitian yang terus menemukan bahwa terdapat hubungan positif antara malu (secara umum) dan patologi makan (Gee & Troop, 2003;Grabhorn, Stenner, Stangier, & Kaulfhold, 2006;Masheb, Grilo & Brondolo, 1999;Murray, Waller & Legg, 2000;Sanftner, Barlow, Marschall, & Tangney, 1995;Swan & Andrews, 2003;Troop, Allan, Serpell, & Treasure, 2008).…”
Section: ; Bulimia Nervosa (Bn); Binge Eating Disorder (Bed); Dan Eatunclassified
“…Shame is significantly associated with eating psychopathology symptoms in nonclinical (e.g., Gee and Troop, 2003;Murray et al, 2000;Sanftner et al, 1995) and in clinical samples with eating disorders (Duarte et al, 2016;Grabhorn et al, 2006;Swan and Andrews, 2003). More specifically, Duarte et al (2014), in a study conducted in a nonclinical sample of women from the general population, found that body shame had a significant effect on binge eating symptoms, above overall negative affectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Literature has consistently linked high levels of shame to psychosocial impairment and a wide range of psychopathological conditions [e.g., 23,26], namely eating disorders [27][28][29][30]. In fact, shame may trigger a series of defensive responses (aiming to correct features or attitudes perceived as defective), such as self-directed negative affect and self-judgmental attitudes [31].…”
Section: Introductionmentioning
confidence: 99%